Pulmonary Sclerosing Pneumocytoma; A Frozen Section Diagnostic Dilemma. (9th November 2022) - Zenezan, D; Tabet, G; Mollaee, M; Akhtar, I
Abstract: Introduction/Objective: Pulmonary Sclerosing Pneumocytoma (PSP)is a benign neoplasm with features of pneumocytic differentiation and dual-cell population. It is a rare tumor of adults with female predilection. The tumor is mostly asymptomatic. However, it can rarely show pleural invasion or lymph node metastasis. Presenting as a mass lesion by imaging studies frequently mandates a frozen section, which can be extremely challenging, and misdiagnosed as lung adenocarcinoma. We report a case of PSP with focal visceral pleural invasion that was submitted for frozen section. Methods/Case Report: We report a case of a 57- year old female found to have a 2.5 cm nodule of the right lower lobe of lung on the CT scan. The patient underwent a wedge resection and the specimen was sent for intraoperative diagnosis. Sectioning revealed a firm, tan-white lesion measuring 2.1 x 2.0 x 1.1 cm. Frozen section diagnosis was suggestive of lepidic pattern adenocarcinoma with areas of fibrosis. Respectively, permanent section of the lesion revealed sheets of bland appearing cuboidal cells lining the papillary and sclerotic areas with round, bland appearing cells within the stroma. A few cells showed mild cytologic atypia with occasional prominent nucleoli and scattered mitotic figures were noted, besides visceral pleural invasion. Foci of atypical adenomatous hyperplasia were noted in close vicinity raising the suspicion of lepidic pattern adenocarcinoma on frozen section.The immunohistochemical staining was positive for Napsin, keratin, and CK7 in the surface cells but not in the round cells and EMA immunostain highlighted the surface cells and scattered round cells. Additional immunostains showed expression of estrogen receptor in the round cell component and TTF1 in both the round and surface components. The immunoprofile further supported the diagnosis of PSP and the elastic stain highlighted the visceral pleural involvement. Combined morphology and immunoprofile supported the diagnosis of PSP. Results (if a Case Study enter NA): NA Conclusion: PSP is a rare benign neoplasm. It is important to recognize this challenging entity during intraoperative diagnosis as it can be easily mistaken for lung adenocarcinoma, especially in the presence of pleural invasion. The best treatment is still surgery for this neoplasm.